Comparative Efficacy of Microneedling with and without Topical Vitamin D3 in Localized Alopecia areata - Rameen Masood; Faria Asad; Hira Tariq; Uzma Amin; Abrar Ul Haq (Pakistan Journal of Health Sciences, 2026)
Alopecia areata represents a T-cell-mediated autoimmune disorder causing non-scarring hair loss. While microneedling demonstrates therapeutic potential, adjunctive strategies to enhance efficacy remain underexplored. Objectives: To compare the efficacy and safety of microneedling combined with topical vitamin D3 versus microneedling monotherapy in localized alopecia areata. Methods: An open-label randomized controlled trial enrolled 80 participants (April–October 2025) with localized patchy alopecia areata affecting